Shortest Path Methods for Automated Warehouse Applications - Vivaldini, K. C. T.; Becker, M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
In materials handling activities, finding the best route for vehicles is a key factor for the improvement of productivity and efficiency and, reduction of costs. The shortest path is the most common criterion adopted in a routing problem. The difficulty in solving this problem is due to a large number of nonoptimal solutions. The best path is not always found if the quantity of maneuvers is not taken into account in the route. This paper reports a comparison of Dijkstra and Network Simplex Algorithms, and propose a modified version of Dijkstra’s Algorithm to reduce the number of vehicle maneuvers. In the results, as the environment complexity increased, the differences in the algorithm performances were highlighted.